An investigation of isolated bursts of solar radio noise - Shuter, William Leslie Hazlewood (Rhodes University, Faculty of Science, Department of Physics, 1958)
The literature on isolated bursts and possible mechanisms of origin has been critically reviewed, and observations point to a mechanism involving omission of electromagnetc radiation from plasma oscillations in the solar corona excited by outward travelling disturbances. Solar noise observations on 125 Mc./s. recorded at Rhodes University during the period November 26 1957 - February 6 1958 have been analysed by the author for isolated bursts, and these observations show the same general features reported by previous investigators. In interpretation of these records particular attention has been devoted to two aspects of isolated bursts; namely the preponderance on single frequency records of double-humped bursts, and the shape of isolated burst profiles. The authors suggests that a probable explanation of double-humped bursts observed on any frequency f is that the first hump represents omission at or near the level of zero refractive index for f radiation, and that the second hump corresponds to harmonic omission at the f/2 level. Source velocities may be calculated from the time delay between the peaks and an average value of 2 x 10â ´ km./sec. was obtained from an analysis of 21 double-humped bursts. This value is in very good agreement with that deduced by Wild (1950b) from the rate of frequency drift of peak intensity of isolated bursts. Simple isolated bursts had decay profiles which are approximatley exponential in shape, and this is usually interpreted in terms of the natural decay of plasma oscillations in the medium of origin. The author has verified that the exponential function is a good fit to the observed decay profiles, but shows that a relation of the form I - Â¹/n (superscript) â‹‰ t (where I is intensity and t is time) fits just as well. An alternative model is suggested which would lead to an exponential-like decay profile which is not determined by the natural decay of plasma oscillations. The work concludes with some suggestions for further research.
Keywords: Solar physics -- Research; Solar radio emission